Interactive education in public administration (2): Strategies for teachers. (March 2015) - Brock, Jonathan; Alford, John
The previous article ('Interactive education in public administration (1): The role of teaching "objects"') described the benefits of 'moving from behind the lectern' to engage in interactive teaching in public policy and administration, and the central role of 'objects' in that process. But teaching 'objects' can only produce effective results if they are used in a way that achieves learning objectives. Interaction for interaction's sake is not enough; it must also lead to understanding of new concepts and analytical approaches. Moreover, interactive teaching can be challenging for teachers who mainly use didactic traditional lecturing, since it entails sharing control of the discussion with students. This article explains and justifies a purposeful, structured framework both for stimulating engagement in public administration courses, and for turning that engagement into learning, in a way that provides for the intellectual safety of the teacher and student – which is crucial for enabling participants to take risks in classroom discussions. In the process, the article further addresses the rationale for using interactive and object-based approaches specifically in public administration and related disciplines.